Pelatihan Agrowisata Berbasis Komunitas untuk Pemberdayaan Perempuan dan Pemuda di Nagari Aia Dingin, Kabupaten Solok - Rusta, Andri; Asrinaldi; Tengku Rika Valentina; Kevin Philip; Pijar Qolbun Sallim (LP2M INSURI Ponorogo, 2025)
Nagari Aia Dingin, Solok Regency, has excellent agrotourism assets (Arabica coffee, horticulture, buffalo curd with intellectual property rights) but faces obstacles in the form of low human resource capacity and product processing standardization. This initiative aims to enhance the capacity of youth and the Women Farmers Group (KWT) through certified BNSP barista Training of Trainers (ToT), diversification of frozen horticultural products, and strengthening hygienic cheese production. The program integrates Participatory Action Research (PAR) for inclusive collaboration and Theory of Change (ToC) as a logical framework. Evaluation uses a Pre-Experimental Pre-Post Test design on 44 participants (24 youth and 20 KWT), supplemented by observation and FGD. The program's implementation successfully enhanced human resource capacity and infrastructure. Pre-post test results showed an average increase of 48% in technical knowledge and 110% in practical skills among the barista youth group. Vital infrastructure support (barista and frozen food equipment) from PT. PLN UID West Sumatra facilitated the adoption of technology. Socio-economically, the program successfully created BNSP-certified trainers and empowered KWT in processing value-added products, contributing to the achievement of SDGs 5 and 8. The integration of PAR and ToC proved effective in facilitating technology transfer and capacity building in a participatory manner, resulting in a dual impact: potential income growth and the strengthening of local cultural identity. This model is recommended as an adaptive replication model; however, longitudinal studies are necessary to analyze the long-term impacts.